A novel asymmetric three-party based authentication scheme in wearable devices environment. (January 2016) - Liu, Sha; Hu, Shun; Weng, Jian; Zhu, Shuhua; Chen, Zhiyan
Abstract: As we know, wearable devices record data generating from user׳s daily activities, and most of which are private data, such as health data and movement data. These information is usually stored in user׳s device. As more and more people started using wearable devices, some security problems have emerged and not been resolved perfectly, for example, how to keep the sensitive information safely in wearable devices and how to secure the user׳s privacy is becoming important issues in recent years. Considering the limitation of hardware of wearable devices, implementing authentication among three different parties (wearable devices, mobile terminals and users) would be a practical way to address these problems effectively. However, based on our study, traditional lightweight authentication schemes could not be applied for this new environment directly. In this paper, we proposed an asymmetric three-party based authentication scheme in this new environment. Drawing on the visual out-of -band (OOB) channel, two-dimensional code (QR code) and secure device pairing method, our scheme provides a mutual efficient authentication between wearable devices and mobile terminal. We made a new attempt to label the Bluetooth device address into a visual tag in order to reduce the time of Bluetooth connection. In addition, we took the multi-users condition into consideration and allowed primary user to add number of authorized users by authentication process. According to security and usability analysis, we proved that this scheme can not only resist known types of attacks but also can be practically applied in new environment. The experiment result shows thatperformance of the scheme meets our expectations.